Analisis Penggunaan Gaya Bahasa Pada Puisi “Kaleidoskop” Karya Salman Khairy Farras Dalam Buku Antologi Puisi Lembah Rasa - Rizal Putra Pratama (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This article discusses the poem “Kaleidoscope” by Salman Khairi Faras in the book: Anthology of Poetry of the Valley of Taste. The poem will be discussed by analyzing the style of language contained in the poem. This study uses a structural approach by analyzing the elements that build literary works from within. The method used in this research is a qualitative method by specifying poetry as a data source and research object. The purpose of this study is to describe the use of language style in the poem “Kaleidoscope” by Salman Khairi Faras in the book Anthology of Poems of Lembah Rasa.The benefits of this research are to provide insight to readers in terms of literary works, to become a source of reference for further research, and as a comparison for future researchers in developing relevant research. The results of this study indicate that the poem “Kaleidoscope” by Salman Khairi Faras in the book: Anthology of Poems of Lembah Rasa has several styles of language. The style of language is personification, association, hyperbole, metaphor and antonomasia. The dominant style of language in the poem “Kaleidoscope” by Salman Khairy Farras is personification, hyperbole and metaphor.